Investigating Privacy Preserving Healthcare Social Network - Memon, Qurban A; Mustafa, Asma Fayes (Discoveries in Agriculture and Food Sciences, 2015)
As health information is valuable, thieves will continue to steal it. Likewise, insufficiently trained employees at organizations or even individuals that pay less attention to creating a privacy-aware culture will suffer data losses when unprotected devices are lost, stolen or sniffed. In this work, sensors are exploited to collect and generate data to be processed, clustered and shared via locally developed application to improve social networking in context of privacy preserving healthcare. The solution is developed for Android operating system. It provides the user with a set of network related social services. In addition to (i) showing specific places (ii) sharing the user location; (iii) showing nearby friends; (iv) getting and sharing weather temperature, it clusters nearby friends; calculates and shares distance moved, calories burned and active time; calculates tracking and shares the user heart rate,. Data privacy model is presented using data session levels and user roles to ensure privacy within healthcare social network.